From Influenza Virus to Novel Corona Virus (SARS-CoV-2)–The Contribution of Obesity - Bhattacharya, Indranil; Ghayor, Chafik; Pérez Dominguez, Ana; Weber, Franz E. (Frontiers in Endocrinology, 2020)
From the beginning of 2020, the governments around the World are tackling a large number of infections and fatalities caused by the novel severe acute respiratory syndrome coronavirus virus (SARS-CoV-2). This virus pandemic has become more complicated as many individuals with diabetes, cardiovascular conditions and obesity are at high risk of acquiring infection and require hospitalization. Prolonged viral infection and obesity, and its associated conditions are individually known to lower the immune response and a combination can thus result in a substantial weakening of the immune system. With the rise in obese individuals globally, the chances that these individuals will be at a risk of infection is heightened. In this review, we discuss how obesity, a low-grade chronic inflammation, can be an ideal environment to promote viral infection. We look at the many lessons learnt from the 2009 H1N1 influenza A pandemic and relate it to the very little information that is available on SARS-CoV-2 infected individuals with overweight and obesity. The objective of this review article is to shed light on why obesity, a pandemic built over many years, deteriorates lung function and favors viral infection resulting in severe health and economic consequences.